BENTUK DAN MAKNA MAJAS HIPERBOLA DALAM LIRIK LAGU PADA MINI ALBUM MAKEINU NI ANKOURU WA IRANAI KARYA YORUSHIKA - Nur Prihandika, Dwi; Syahrial; Kartika, Diana; Immerry, Tienn (Hikari: Jurnal Bahasa dan Kebudayaan, 2024)
Hyperbole is a figure of speech that describes or narrates an event by exaggerating it. This figure of speech aims to present the event more dramatically, attractively, beautifully, and similar way. The type of meaning in this research uses shifting meaning, that is the symptoms of expansion, narrowing, connotation, synesthesia, and association of a word meaning that is still alive in one field of meaning. This research discusses hyperbolic figures of speech and shifting meaning contained in the song lyrics sung by Yorushika from the mini album Makeinu ni Ankouru wa Iranai using Claridge and Parera’s theory. Claridge's theory is a hyperbolic figure of speech which is divided into 7 forms, while Parera's theory is a shifting meaning. This research identifies 7 forms of hyperbole, namely, Single-word Hyperbole, Phrasal Hyperbole, Clausal Hyperbole, Numerical Hyperbole, The Role of The Superlative, Comparison, Repetition. This research method is descriptive research used to describe hyperbole and meaning in Yorushika song lyrics, the data collection technique used is the simak catat technique, and to analyze the data the author uses the basic technique of agih method (BUL).This research found a total 29 data, where Single-word Hyperbole (one word hyperbole) was more frequently found with 13 pieces of data, in the word class there were verbs and the most frequently found shifting meaning was the connotation meaning.